Trabectedin for metastatic soft tissue sarcoma: a retrospective single center analysis - Schmitt, Thomas; Keller, Eva; Dietrich, Sascha; Wuchter, Patrick; Ho, Anthony Dick; Egerer, Gerlinde (Marine drugs, 2010)
Soft tissue sarcoma (STS) comprises a large variety of rare malignant tumors. Development of distant metastasis is frequent, even in patients undergoing initial curative surgery. Trabectedin, a tetrahydroisoquinoline alkaloid isolated from the Caribbean marine tunicate Ecteinascidia turbinata, was approved in 2007 for patients with advanced STS after failure of anthracyclines and ifosfamide, or for patients unsuited to receive these agents. In this study, we retrospectively analyzed 25 patients who had been treated with trabectedin at our institution between 2007 and 2010.
Gesehen am 15.06.2023